Citizen Welfare: the Effect of revenue on the Nigeria Economy - Akinyede, Oyinlola (Innovations, 2022)
Citizen welfare synonymous with state welfare provides stability and comfort in a country's social-economic index. This study used Nigerian citizens' economic and social factors as its foundation to analyse the impact of tax income on Nigerians. Secondary Data was sourced from relevant sources. Total tax revenue TAX is the independent variable. At the same time, citizen welfare is proxied by consumer prices (CON) and Unemployment (EMP) for economic welfare and health (HEA) and Education (EDU) for social welfare. In addition, there is a substantial correlation between tax income.The result demonstrates a significant correlation between tax revenue and the unemployment rate (0.000) and between tax revenue and government spending on education (0.00). In addition, there is a substantial correlation between tax and government spending on health (GSH) in Nigeria, with a significant rate of 0.012 and a significant association between tax and inflation (CPI).The study suggests the Nigerian government invest more in the economic and social wellbeing of its residents because improved citizen welfare directly affects taxes, which has a direct impact on the development